THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN TEACHING ENGLISH READING COMPREHENSION AT 11 GRADE STUDENTS OF SMA MATHLA’UL ANWAR - Melyadi, Rian; Fadloeli, Odo (PROJECT (Professional Journal of English Education), 2019)
The aim of the research is to improve students’ reading comprehension through a scientific approach. The research was conducted at SMA Mathla’ul Anwar in the first semester. The researcher used the method of the research is qualitative research, a classroom action research. The research used three cycles. Any cycle exists in four steps. There are planning, action, observation, and reflection. The subjects of the research were 32 students at XI IPA 1 of SMA Mathla’ul Anwar. The researcher collected the data using observation, interview, test, and discussion to collect data that need at the time of the study. It determined the extent of the increase students’ reading comprehension before and after the following scientific approach. most of them have low motivation in the learning activity. Students whose English are good enough have good motivation in the learning activity. Most of the students have low willingness to learn especially when they entered the noon hour lesson.The analysis of the research data showed that there was an increase in the average and percentage students’ score, from the score in cycle I am 65 or 37.5%, cycle II is 71 or 59%, cycle III is 80 or 100%. It can be said that scientific approach improved students’ reading comprehension at XI IPA 1 of SMA Mathla’ul Anwar in Academic 2018/2019.Keywords:  Students, Improving reading comprehension, Scientific approach.